Speckled leukoplakia- case report and review of literature - Melisha Rolita Pinto; Poorvi Yadav; Sutapa Maity; Akash Kumar Pal (Journal of Orofacial Research, 2020)
Oral leukoplakia is the most common potentially malignant disorder of the oral cavity. Non homogenous forms of leukoplakia has the higher rates of malignant transformation. Although clinical diagnosis is the most commonly sought form of diagnosis, incisional biopsy with scalpel and histopathological examination is the gold standard for diagnosis, planning treatment, and for ascertaining the prognosis of the lesion. Hereby, we report a case of speckled leukoplakia which was histopathologically diagnosed as carcinoma in situ and managed with surgical excision with skin graft and concomitant chemopreventive agents.